Recursos directamente recaudados y su influencia en la ejecución de gastos en la municipalidad distrital de Belén, periodo 2018-2022 - Canga Torres, Ana Cecilia (2024)
The Spearman correlation analysis between the income ("RDR") and expenses ("Expense") of the municipality of Belén during the period 2018-2022 showed a coefficient of 0.4000, indicating a moderate positive correlation. However, the associated p value (0.5046) suggests that this correlation is not statistically significant, which implies that there is no strong and consistent relationship between both variables. This result suggests a possible disconnection between income generation and expenditure execution, which could reflect challenges in the municipality's financial planning. External factors, such as economic events or changes in management, could have influenced this lack of correlation. Therefore, it is recommended that the municipality review its budget planning strategies, improve monitoring of external factors and strengthen accountability to ensure greater coherence between revenues and expenditures in the future. Additionally, offering budget management training could improve the municipality's ability to better align its revenues and expenses, thus optimizing financial management.